Evolution of Voltage-Dependent Anion Channel Function: From Molecular Sieve to Governator to Actuator of Ferroptosis - Lemasters, John J. (Frontiers in Oncology, 2017)
The voltage dependent anion channel (VDAC) is well known as the pathway for passive diffusion of anionic hydrophilic mitochondrial metabolites across the outer membrane, but a more complex functionality of the three isoforms of VDAC has emerged, as addressed in the Frontiers in Oncology Research Topic on “Uncovering the Function of the Mitochondrial Protein VDAC in Health and Disease: From Structure-Function to Novel Therapeutic Strategies”. VDAC as the single most abundant protein in mitochondrial outer membranes is typically involved in isoform-specific interactions of the mitochondrion with its surroundings as, for example, during mitochondria-dependent pathways of cell death. VDAC closure can also act as an adjustable limiter (governator) of global mitochondrial metabolism, as during hepatic ethanol metabolism to promote selective oxidation of membrane-permeant acetaldehyde. In cancer cells, high free tubulin inhibits VDAC1 and VDAC2, contributing to suppression of mitochondrial function in the Warburg phenomenon. Erastin, the canonical inducer of ferroptosis, opens VDAC in the presence of tubulin and hyperpolarizes mitochondria, leading to mitochondrial production reactive oxygen species, mitochondrial dysfunction and cell death. Our understanding of VDAC function continues to evolve.